Effect of Feeding Bentonite Clay (Smectite) on Excretion of Aflatoxin M1 in Milk of Dairy Animals - Sherasia, Pankaj Lakshmanbhai; Waghela, Chanchal; Sharma, Rajesh; Patel, Ashok; V Sridhar; Pawar, Prashant; Gupta, Shashikant (Indian Journal of Animal Nutrition, 2024)
Aim of this field study was to evaluate the effect of feeding sodium bentonite on feed intake, milk yield, excretion of aflatoxin M1 and mineral bioavailability in dairy animals. Thirty multiparous lactating cows and buffaloes (10-15 kg milk/day) were divided into three groups (Control, T1 and T2) of ten each, based on milk yield, fat% and stage of lactation (90-180 post calving). All animals were daily fed basal diet comprising 3-4 kg cattle feed, 2-3 kg maize bhardo, 15-20 kg hybrid napier fodder and 4-5 kg jowar straw. In addition to basal diet, each animal in treatment groups T1 and T2 were daily supplemented 100 and 150 g sodium bentonite clay (montmorillonite-87.67%; in vitro net binding capacity-97.59%), respectively. Dry matter intake, milk yield, aflatoxin B1 intake and excretion of aflatoxin M1 of individual animals were recorded on day 0, 15, 30, 45 and 60. Blood samples were collected before (0 day) and after (60 days) feeding sodium bentonite. Study revealed that supplementation of sodium bentonite did not affect (P>0.05) dry matter intake and milk yield. Average aflatoxin B1 intake was 83.17, 89.38 and 105.95 µg/kg dry matter intake in control, T1 and T2 groups, respectively. Supplementation of sodium bentonite @ 100 and 150 g in the ration of dairy animals significantly (P